The birth of an organisational field: the institutionalisation of civilian crisis response services in the de-tasking era - Giacomantonio, Chris (Policing and society, 2024)
Civilian-led, non-police crisis response services – which attend mental health crises that previously had received uniformed police response in many jurisdictions – have multiplied substantially alongside widespread calls for ‘de-tasking’ of police. Yet, these services inevitably engage in forms of ‘policing’ in both practical and sociological terms, if we understand policing to involve reducing harms and maintaining order under the shadow of police (state coercive) power. Seeing the rapid expansion of these services as the birth of a new organisational field, following organisational and institutional theories, this paper delineates possible futures of these services as they coalesce into increasingly isomorphic forms. The paper then considers the potential bases of legitimacy, organisational ethos and accountability that will develop around these services, and sets out challenges that the organisational field will face if it is to avoid becoming an extension of ‘the police’.